Anethole Exerts Antimetatstaic Activity via Inhibition of Matrix Metalloproteinase 2/9 and AKT/Mitogen-Activated Kinase/Nuclear Factor Kappa B Signaling Pathways - Eun Jeong Choo; Yun‐Hee Rhee; Soo‐Jin Jeong; Hyo‐Jung Lee; Hyun Seok Kim; Hyun Suk Ko; Ji‐Hyun Kim; Tae‐Rin Kwon; Ji Hoon Jung; Jin Hyoung Kim; Hyo‐Jeong Lee; Eun‐Ok Lee; et al. (2011)
Anethole is known to possess anti-inflammatory and anti-tumor activities and to be a main constituent of fennel, anise, and camphor. In the present study, we evaluated anti-metastatic and apoptotic effects of anethole on highly-metastatic HT-1080 human fibrosarcoma tumor cells. Despite weak cytotoxicity against HT-1080 cells, anethole inhibited the adhesion to Matrigel and invasion of HT-1080 cells in a dose-dependent manner. Anethole was also able to down-regulate the expression of matrix metalloproteinase (MMP)-2 and -9 and up-regulate the gene expression of tissue inhibitor of metalloproteinase (TIMP)-1. The similar inhibitory effect of anethole on MMP-2 and -9 activities was confirmed by zymography assay. Furthermore, anethole significantly decreased mRNA expression of urokinase plasminogen activator (uPA), but not uPA receptor (uPAR). In addition, anethole suppressed the phosphorylation of AKT, extracellular signal-regulated kinase (ERK), p38 and nuclear transcription factor kappa B (NF-κB) in HT-1080 cells. Taken together, our findings indicate that anethole is a potent anti-metastatic drug that functions through inhibiting MMP-2/9 and AKT/mitogen-activated protein kinase (MAPK)/NF-κB signal transducers.